Sagittal plane motion of the lumbar spine during ergometer and single scull rowing - Wilson, F.; Gissane, C.; Gormley, J.; Simms, C. (Sports Biomechanics, 2013)
Lumbar spine injury in rowers is common and ergometer rowing has been cited as a risk factor for this injury. The purpose of this study is to compare lumbar kinematics between ergometer and single scull rowing and to examine the effect of fatigue on kinematics. The sagittal lumbar spine motion of 19 elite male rowers (lumbar spine injury free in the previous six months) was measured with an electrogoniometer during a `step test` on an ergometer and in a single sculling boat. Maximum range of lumbar flexion was recorded in standing for reference. Power output and heart rate were recorded during the ergometer tests. Heart rate was used as a surrogate for power output in the sculling test. Maximum lumbar flexion increased during the step test and was significantly greater on the ergometer (4.4° ± 0.9°change), compared with the boat (+1.3° ± 1.1°change), (3.1°difference, p = 0.035). Compared to the voluntary range of motion, there is an increase of 11.3% (ergometer) and 4.1% (boat). Lumbar spine flexion increases significantly during the course of an ergometer trial while changes in a sculling boat were minimal. Such differences may contribute to the recent findings linking ergometer use to lower-back injury.